Formaldehyde in indoor air: a public health problem? - Viegas, Susana (2012)
Formaldehyde was the first air pollutant, which already in the 1970s emerged as a specifically non-industrial indoor air quality problem. Yet formaldehyde remained an indoor air quality issue and the formaldehyde level in residential indoor air is among the highest of any indoor air contaminant. Formaldehyde concentrations in 4 different indoor settings (schools, office buildings, new dwellings and occupied dwellings) in Portugal were measured using Photo Ionization Detection (PID) equipment (11,7 eV lamps). All the settings presented results higher than the reference value proposed by Portuguese legislation. Furthermore, occupied dwellings showed 3 units with results above the reference. We could conclude that formaldehyde presence is a reality in monitored indoor settings. Concentration levels are higher than the Portuguese reference value for indoor settings and these can indicate health problems for occupants.